2021
DOI: 10.17691/stm2021.13.3.08
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Injury Molecule 1 (KIM-1): a Multifunctional Glycoprotein and Biological Marker (Review)

Abstract: KIM-1 (kidney injury molecule 1) is a transmembrane glycoprotein also known as HAVcr-1 and TIM-1 belongs to the T-cell immunoglobulin and mucin domain family (TIM) of proteins. TIM glycoproteins are presented on the immune cells and participate in the regulation of immune reactions. KIM-1 differs from other members of its family in that it is expressed not only by immunocompetent cells but epithelial cells as well. Cellular and humoral effects mediated by KIM-1 are involved in a variety of physiological and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 139 publications
1
27
0
1
Order By: Relevance
“…Hypoxia is a powerful stimulus for KIM-1 expression in the proximal tubular cells. The upregulation of KIM-1 increases the release of cytokines and chemokines, that enhances inflammation, hypoxia and fibrosis, thus aggravating the CKD [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is a powerful stimulus for KIM-1 expression in the proximal tubular cells. The upregulation of KIM-1 increases the release of cytokines and chemokines, that enhances inflammation, hypoxia and fibrosis, thus aggravating the CKD [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was suggested that the phagocytotic function of KIM-1 may be adapted by RCC cells to clear tumor apoptotic bodies, thus preventing the activation of APCs and T lymphocytes against RCC cells. In other words, KIM-1 may play a scavenger role in RCC against potential immune reactions and may be a key factor in the tumor microenvironment for the survival and development of RCC (14)(15)(16)(17). KIM-1 overexpression in the cells of clear cell and papillary RCC has for a long time been known as a special feature of kidney tumors, but data concerning the clinical significance of increased KIM-1 expression in the extra-renal tumors are ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…TIM-1, one of these proteins, is homologous to KIM-1. In summary, the definitions of HAVcr-1, KIM-1 and TIM-1 (CD365) mentioned in the biological databases today describe the same protein (14)(15)(16). KIM-1 is normally expressed at a low level in the healthy kidney.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations